Paulus se vernuftige vervlegting van antropologie en eskatologie in 2 Korintiërs 4:7-5:10 - Du Rand, Jan A. (Verbum et ecclesia, 1999)
It has been said that Paul is not really Pauline in his eschatological thoughts in 2 Corinthians 4:7-5:10. What could be the reasonfor that? The discourse is very personal. What emerges in the foreground are Paul's tribulations and suffering in his apostolic ministry. It is narrated in such a way that it forms the basis for understanding his anthropology and eschatology. His apostolic existence runs between two poles: his faith in Christ and his eschatological hope. Therefore, his anthropology is only to be understood in the light of his eschatology and his eschatology in the light of his anthropology.